Vaccines against norovirus: state of the art trials in children and adults. (1st December 2016) - Baehner, F.; Bogaerts, H.; Goodwin, R.
Abstract: Noroviruses (NoVs), a group of nonenveloped, single-stranded RNA viruses belonging to the Caliciviridae family, are the leading cause worldwide of acute infectious gastroenteritis. Serious and eventual fatal outcomes may be observed in at-risk populations such as the very young or older adults, especially in those with underlying diseases. NoVs are highly infectious, with a low number of virus particles causing infection, and they are highly resistant to environmental conditions. NoVs have multiple routes of transmission including faecal–oral, aerosolized vomitus, person to person and via contaminated surfaces or food and water. NoVs can cause frequent and dramatic outbreaks where people congregate in close quarters such as hospitals, long-term care facilities, cruise liners and military barracks and ships. Of the seven NoV genogroups, human disease is most frequently caused by genogroups I and II, although genogroup IV has also been associated with illness. The absence of reliable, high-yield cell culture systems or animal models has steered the development of vaccines towards nonreplicating recombinant capsid proteins including viruslike particles and the sub-virus-sized P particles. Takeda Vaccines is developing a candidate NoV vaccine formulation based on adjuvanted viruslike particles from the GI.1 genotype and a consensus GII.4 sequence derived from three natural GII.4 variants. Early clinical trial results show good tolerability and robust immune responses to both components. This approach is designed to induce broad protective immune responses in adults and children.